Research on active collision avoidance algorithm for intelligent vehicle based on improved artificial potential field model. (8th May 2020) - Yuan, Chaochun; Weng, Shuofeng; Shen, Jie; Chen, Long; He, Youguo; Wang, Tong
In this article, an active collision avoidance based on improved artificial potential field is proposed to satisfy collision avoidance for intelligent vehicle. A longitudinal safety distance model based on analysis of braking process and a lane-changing safety spacing model based on minimum time of lane changing under the constraint of sideslip angle are presented. In addition, an improved artificial potential field method is introduced, which represents the influence of environmental information with artificial force. Simulation results demonstrate the superior performance of the proposed algorithm over collision avoidance for intelligent vehicle.